Technologies of Exposure: Videoconferenced Distributed Medical Education as a Sociomaterial Practice. (March 2019) - MacLeod, Anna; Cameron, Paula; Kits, Olga; Tummons, Jonathan
Abstract : Purpose: Videoconferencing—a network of buttons, screens, microphones, cameras, and speakers—is one way to ensure that undergraduate medical curricula are comparably delivered across distributed medical education (DME) sites, a common requirement for accreditation. However, few researchers have critically explored the role of videoconference technologies in day-to-day DME. The authors, therefore, conducted a three-year ethnographic study of a Canadian undergraduate DME program. Method: Drawing on 108 hours of observations, 33 interviews, and analysis of 65 documents—all collected at two campuses between January 2013 and February 2015—the authors explored the question, "What is revealed when we consider videoconferencing for DME as a sociomaterial practice?" Results: The authors describe three interconnected ways that videoconference systems operate as unintended "technologies of exposure": visual, curricular, and auditory. Videoconferencing inadvertently exposes both mundane and extraordinary images and sounds, offering access to the informal, unintended, and even disavowed curriculum of everyday medical education. The authors conceptualize these exposures as sociomaterial practices, which add an additional layer of complexity for members of medical school communities. Conclusions: This analysis challenges the assumption that videoconferencing merely extends the bricks-and-mortar classroom. The authors discuss practical implications and recommend more critical consideration of the ways videoconferencing shifts the terrain of medical education. These findings point to a need for more critically oriented research exploring the ways DME technologies transform medical education, in both intended and unintended ways. Abstract : Supplemental Digital Content is available in the text.